(untitled) (PERcursos Linguísticos, 2021)
The work presentes a syntesis of how the first studies about conversation were stablished from the work of Garfinkel – Studies in Etnomethodology – published in 1967. In Brazil these studies started in the 1980 from the last century with the first studies on Textual Linguistics and Conversation Analysis that examined elements of speech, with the markers, the topic, the shift. In a second moment, almost concomitant, interest movies to the structural organization of the conversation, in a more specifically linguistic approach, seeking to reveal the sistematicities of the language. Then the first theses and dissertations appear and several research groups are constitued.The work also focuses on the issue of teaching orality in the classroom, with suggetions of activities, emphasizing that knowledge about the concepto of spoken and written language is not enough: it is necessary that the teacher has subsides in relation to the specificities of the texts that circulate in society, in determined discourse domains.